Incidental genomic findings in large scale research: using the “3-I framework” to reveal policy considerations - Onstwedder, Suzanne Maria; Van El, Carla; Rodenburg, Wendy; Thorogood, Adrian; Cornel, Martina Cornelia; Rigter, Tessel (Frontiers in Genetics, 2026)
IntroductionIncidental findings (IF) can be yielded in genomic research that analyzes data from healthy participants or patients. The need for clear IF policies grows along with the increase in international genomic research, data collection and sharing efforts. This study aims to inform policy discussions and decisions about IF.MethodsWe interviewed key stakeholders involved in Canadian, European, or international research projects. We used the 3-I framework for interview design and analysis, which distinguishes interests (i.e., agendas), ideas (i.e., values), and institutions (i.e., policy structures, e.g., laws) as factors that impact policy decisions. We integrated the three bioethical principles into this framework: respect for persons, beneficence, and justice.ResultsInterviewees were from Canada (n = 7) and Europe (n = 4). Different IF policies are followed and practiced. Policy decisions are impacted by varying interests, ideas, and institutions. Prioritization of distinct interests and ideas varies between policies. Key policy considerations are: determining whose interest is prioritized; determining what is of best interest to the participant; determining who is responsible for what when research and healthcare institutional frameworks create tension; determining what is just and a fair distribution of benefits and burdens between individuals and populations; and determining how scarce time and money should be allocated.DiscussionExplicating policy considerations can help to further discuss and decide how IF policies will impact not only research participants, but also patients, citizens, professionals, the public and diverse populations. Technologies, cultural values, and laws and regulations evolve over time. Therefore, continuous discussions should be held.